Proteasome-dependent degradation of transcription factor activating enhancer-binding protein 4 (TFAP4) controls mitotic division. - D'Annibale, S; Kim, J; Magliozzi, R; Low, T; Mohammed, S; Heck, A; Guardavaccaro, D (American Society for Biochemistry and Molecular Biology Inc., 2014)
TFAP4, a basic helix-loop-helix transcription factor that regulates the expression of a multitude of genes involved in the regulation of cellular proliferation, stemness, and epithelial-mesenchymal transition, is up-regulated in colorectal cancer and a number of other human malignancies. We have found that, during the G2 phase of the cell division cycle, TFAP4 is targeted for proteasome-dependent degradation by the SCF(βTrCP) ubiquitin ligase. This event requires phosphorylation of TFAP4 on a conserved degron. Expression of a stable TFAP4 mutant unable to interact with βTrCP results in a number of mitotic defects, including chromosome missegregation and multipolar spindles, which eventually lead to the activation of the DNA damage response. Our findings reveal that βTrCP-dependent degradation of TFAP4 is required for the fidelity of mitotic division.